Mother’s Status and the Prevalence of Smoking Habits among Adolescents: A Survey in Pontianak City, Indonesia - Massardi, Restiatun (Jurnal Ekonomi Kuantitatif Terapan; 2020: Vol. 13, No.2, Agustus 2020 (pp.211-356), 2020)
The smoking rate of adolescent continues to increase in Indonesia. It is necessary to involve all parties in the anti-smoking campaign, including mothers.This research aims to find out about the influences of mother’s status on the prevalence of smoking habits among adolescent. Mother’s status in this research referred to education level and occupation status. This research data was obtained from a survey questionnaire with 998 adolescent respondents in Pontianak City, Indonesia. The research findings showed that only mother’s occupation status significantly influences the probability for mothers to give some suggestions to their children about the danger of smoking. However, mother’s suggestion variable did not significantly influence their children’s decision to smoke. But the significant variables to influence adolescents’ decision to smoke were smoking parents and father’s suggestions about the danger of smoking.This is due to the culture of Indonesian society, children tend to more obey their fathers’ advice than their mothers’ ones. Keywords: Adolescent; Smoking Habit; Mother’s status, Education level, Occupation status.